Molecular epidemiology of Campylobacter jejuni populations in dairy cattle, wildlife, and the environment in a farmland area - Kwan, Patrick S L; Barrigas, Mishele; Bolton, Frederick J; French, Nigel P; Gowland, Peter; Kemp, Richard; Leatherbarrow, Howard; Upton, Mathew; Fox, Andrew J (Applied and environmental microbiology, 2008)
We describe a cross-sectional study of the molecular epidemiology of Campylobacter jejuni in a dairy farmland environment, with the aim of elucidating the dynamics of horizontal transmission of C. jejuni genotypes among sources in the area. A collection of 327 C. jejuni isolates from cattle, wildlife, and environmental sources in a 100-km(2) area of farmland in northwest England was characterized by multilocus sequence typing. A total of 91 sequence types and 18 clonal complexes were identified. Clonal complexes ST-21, ST-45, and ST-61, which have been frequently associated with human disease, were the most commonly recovered genotypes in this study. In addition, widely distributed genotypes as well as potentially host-associated genotypes have been identified, which suggests that both restricted and interconnecting pathways of transmission may be operating in the dairy farmland environment. In particular, the ST-61 complex and the ST-21 complex were significantly associated with cattle. In contrast, complex strains ST-45, ST-952, and ST-677 were isolated predominantly from wild birds, wild rabbits, and environmental water. A considerable number of novel sequence types have also been identified, which were unassigned to existing clonal complexes and were frequently isolated from wildlife and environmental sources. The segregated distribution of genotypes among samples from different sources suggests that their transmission to humans is perhaps via independent routes. Insight into the dynamics and interactions of C. jejuni populations between important animal reservoirs and their surrounding environment would improve the identification of sources of Campylobacter infection and the design of control strategies.